(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The article presents an overview of the current widespread use of pesticides in agricultural enterprises and other veterinary institutions, as well as measures to study their toxic effects on the body of animals and its prevention.